Optimization of the Fluorescent Protein Expression Level Based on Pseudorabies Virus Bartha Strain for Neural Circuit Tracing - Jia, Fan; Lv, Pei; Miao, Huan; Shi, Xiangwei; Mei, Hongjun; Li, Li; Xu, Xiaoqin; Tao, Sijue; Xu, Fuqiang (Frontiers in Neuroanatomy, 2019)
Mapping the neural circuits facilitates understanding the brain’s working mechanism. Pseudorabies virus (PRV; Bartha stain) as a tracer can infect neurons and retrogradely transport in neural circuits. To illuminate the network, tracers expressing reporter genes at a high level are needed. In this study, we optimized the expression level of reporter genes and constructed two new retrograde trans-multisynaptic tracers PRV531 and PRV724, which separately express more robust green and red fluorescent proteins than the existing retrograde tracers PRV152 and PRV614. PRV531 and PRV724 can be used for mapping the neural circuit of the central nervous system (CNS) and the peripheral nervous system (PNS). Overall, our work adds two valuable tracers to the toolbox for mapping neural circuits.